2018
DOI: 10.1590/1678-4162-9453
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of Neospora caninum among goats (Capra hircus) in the state of Paraíba, northeastern Brazil

Abstract: Although goat dairy farms in Brazil may have a higher risk of infection by Neospora caninum than beef farms, risk factor evaluation on a representative population remains to be fully established in Brazil. Accordingly, this study aimed to establish the occurrence of anti-N. caninum antibodies and factors associated with exposure in 406 blood samples from five dairy and three beef goat farms in the state of Paraíba, northeastern Brazil. Anti-N. caninum antibodies were detected by indirect immunofluorescence ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
4
5
0
Order By: Relevance
“…In addition, it was not a significant association between reproductive impairment and toxoplasmosis and/or neosporosis. Similar results are observed with N. caninum prevalence in goats of Paraíba state (Braz et al, 2018); however, it was contrary with other studies about T. gondii.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…In addition, it was not a significant association between reproductive impairment and toxoplasmosis and/or neosporosis. Similar results are observed with N. caninum prevalence in goats of Paraíba state (Braz et al, 2018); however, it was contrary with other studies about T. gondii.…”
Section: Resultssupporting
confidence: 64%
“…Another parasite that can cause reproductive problems is Neospora caninum, first described in 2004 by Figliuolo et al (2004) that reported the prevalence of 6.4% in goat herds in the state of São Paulo. Since then, several studies have been conducted in other states such Paraíba (3.3%; Faria et al, 2007;and 26.11%;Braz et al, 2018), Rio Grande do Norte (1.05%; Lima et al, 2008), and Pernambuco (64,2%; Tembue et al, 2011;and 2.04%;Arraes-Santos et al, 2016). Although the various serologic studies in Brazilian goats' herds, the reproductive impairment caused by N. caninum is still scarce evaluated (Braz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The study also agreed with the findings of the researcher (Braz et al, 2018) on goat herds from different farms in Brazil, but it differed with (Ghattof and Faraj et al, 2015), the variation in the positive percentages of infected animals is due to the weather and the method of breeding in the fields, taking into account the number of animals in one herd, the density and the size of the sample taken for examination, taking into account the method used in diagnosing the disease. Biochemical tests in goats showed a significant increase in the value of aspartate transaminase (AST) and alanine transaminase (ALT), the rise of these enzymes is due to infection with the parasite, as the canine neosporosis parasite is like other parasites, which causes a clear change in liver enzymes as a result of damage to the liver cells .and abnormality of the cell unite due to pathological lesion made by it .Thus, the study agreed with the researcher (Bottaria et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, N. caninum seropositivity was determined in 1 (0.27%) of 368 goats, which were examined serologically by ELISA method and sampled from several locations of Gevaş region. The prevalence rates determined in the research region have been found in some other studies on goat neosporosis in Türkiye and World (Cayvaz and Karatepe 2011;Utuk and Eski 2017;Braz et al 2018;Chiang et al 2020;Udonsom et al 2020) is lower than the prevalence rates determined. The prevalence of N. caninum infection in goats varies considerably between continents and countries worldwide.…”
Section: Discussionmentioning
confidence: 50%